Identification of Casiopeina II-gly secondary targets through a systems pharmacology approach. (February 2019) - de Anda-Jáuregui, Guillermo; Espinal-Enríquez, Jesús; Hur, Junguk; Alcalá-Corona, Sergio Antonio; Ruiz-Azuara, Lena; Hernández-Lemus, Enrique
Abstract : Graphical abstract: Highlights: We identified 3 features of Casiopeina treatment. Perturbation of signaling pathways related to apoptosis induction. Perturbation of metabolic pathways. Activation of Immunes responses. hese findings may drive new experimental exploration of their role in adverse effects and efficacy of Casiopeinas. Abstract: Casiopeinas are a group of copper-based compounds designed to be used as less toxic, more efficient chemotherapeutic agents. In this study, we analyzed the in vitro effects of Casiopeina II-gly on the expression of canonical biological pathways. Using microarray data from HeLa cell lines treated with Casiopeina II-gly, we identified biological pathways that are perturbed after treatment. We present a novel approach integrating pathway analysis and network theory: The Pathway Crosstalk Network. We constructed a network with deregulated pathways, featuring links between those pathways that crosstalk with each other. We identified modules grouping deregulated pathways that are functionally related. Through this approach, we were able to identify three features of Casiopeina treatment: (a) Perturbation of signaling pathways, related to induction of apoptosis; (b) perturbation of metabolic pathways, and (c) activation of immune responses. These findings can be useful to drive new experimental exploration on their role in adverse effects and efficacy of Casiopeinas.